Expression of a cloned Bacillus thuringiensis crystal protein gene in Escherichia coli. - Schnepf, H E (1987)
The expression in Escherichia coli of a cloned crystal protein gene from Bacillus thuringiensis was investigated through the use of fusions of the crystal protein gene promoter to beta-galactosidase and catechol oxidase genes. Analysis of deletion and insertion derivatives of the crystal protein gene promoter showed that a region of B. thuringiensis DNA located between 87 and 258 base pairs upstream from the transcription initiation site caused reduced transcription from this promoter. Insertion of Tn5 145 base pairs upstream from the transcription initiation site resulted in overproduction of the crystal protein. S1 nuclease mapping experiments failed to detect transcription from an outwardly directed promoter in Tn5, indicating that the overproduction resulted from the disruption or repositioning of the transcription-suppressing region.